Lev Rogi najde srečo / Rogi the Lion Finds Happines / Rogi der Löwe findet Glück - Plohl, Igor (University of Maribor Press, 2019)
The project Listen and Feel was conducted from 15 February to 14 June 2019, under the leadership of Assoc. Prof. Alenka Valh Lopert, PhD (Department of Translation Studies, Faculty of Arts, University of Maribor). Students of various study programs of the Faculty of Arts, Faculty of Education, Faculty of Electrical Engineering, and Faculty of Computer Science and Informatics created unique tactile books called Rogi the Lion Finds Happiness, based on the picture book by mag. Igor Plohl (House Pivec Publishing). The students of Translation Studies translated the Slovene version to English and German. They also recorded audiobooks in all three languages. Other pedagogical mentors, who participated in the project, were Assist. Prof. Jerneja Herzog, PhD (PeF UM), Assist. Prof. Aksinja Kermauner, PhD (Faculty of Education, University of Primorska) and Prof. dr. Tatjana Welzer Družovec (FERI UM). Zala Stanonik (Pivec Publishing) and Darinka Lozinšek (Association of the Blind and Partially Sighted of Slovenia) participated in the project as external partners. The following students took part in the project: Leona Nikolaš, Saša Ul, Agnes Kojc (Translation Studies), Sarah Jerebic (Slovene Language and Literature), Urška Lešnjak, Sara Cetl (Fine Arts), Tina Janžekovič, Andrejka Pek, (Preschool Education), Sara Zmrzlak, Klemen Polanec (Media Communications). The University Press published the books, and the project team first presented them to the public at the University Library. The Listen and Feel project is a project work with non-economic and non-profit sector in local and regional environment Student’s innovative projects for social good 2016–2020. It was financed by The Public Scholarship, development, handicapped and alimony fund of Republic Slovenia together with the European Social Fund of the European Union.